Landslide Susceptibility Mapping Using Analytical Hierarchy Process in Gandaki Province, Nepal - Subedi, Sujan; Bhandari, Krishna Prasad; Sherchan, Bikash; Neupane, Nabaraj (Journal of Engineering and Sciences, 2023)
Nepal has a diverse geography ranging from the majestic Himalayas to the fertile plains in the Terai and this varied topography makes it susceptible to different hazards. This study analyzed the most recurring destructive natural hazard, i.e., a landslide in Gandaki Province. The result has been presented using Geographic Information System (GIS) based susceptibility mapping employing Analytical Hierarchy Process (AHP). The susceptibility mapping was performed based on 11 conditioning parameters under four groups, mainly topographic factors (Elevation, Slope, Land Use Land Cover and Profile curvature), hydrological factors (Proximity to stream, Precipitation, Drainage Density and Topographic Wetness Index), geological factors (Geology and Fault lines) and infrastructure factor (Proximity to the road). The final result was classified into five classes: shallow, low, moderate, high, and high susceptibility. The validity and accuracy were tested by calculating the areas under the curve (AUC) value of the receiver operating characteristic (ROC) curve. The AUC value of the landslide was found to be 0.793, indicating the model’s good performance. The final map can be used for disaster risk reduction, land use planning and early warning systems.